A Case of Photoimmunotherapy for Nasopharyngeal Carcinoma Requiring Emergency Tracheostomy - Yukiomi Kushihashi; Tatsuo Masubuchi; Isaku Okamoto; Chihiro Fushimi; Morio Yamazaki; Hisashi Asano; Reo Aoki; Shota Fujii; Yukiko Asako; Yuichiro Tada (Case Reports in Oncology, 2024)
Introduction: Photoimmunotherapy (PIT) is a treatment wherein intravenous cetuximab sarotalocan sodium is administered followed by laser light irradiation. This treatment exhibits a specific antitumor effect if in tumors expressing the epidermal growth factor receptor, regardless of the carcinoma [Mitsunaga et al.: Nat Med. 2011;17(12):1685–91, Sato et al.: ACS Cent Sci. 2018;4(11):1559–69, Nakajima et al.: Cancer Sci. 2018;109(9):2889–96]. The current indications are unresectable, locally advanced, or locally recurrent head and neck cancer. If standard treatments, such as radiotherapy and chemotherapy, are available, they are given priority. However, a significant concern in PIT is the occurrence of airway emergencies related to pharyngeal edema. Prophylactic tracheostomy is often performed in cases of PIT involving the root of the tongue, hypopharynx, or larynx. Case Presentation: In this study, we administered transoral PIT to a patient diagnosed with radiation-induced nasopharyngeal carcinoma (squamous cell carcinoma (SCC) cT1N0M0 stage I). Although previous case reports and our own experiences did not report airway emergencies following PIT for nasopharyngeal carcinoma, a unique case occurred in our study [Omura et al.: Auris Nasus Larynx. 2023;50(4):641–5, Kushihashi et al.: Int J Otolaryngol Head Neck Surg. 2022;11(5, Sep):258–65]. The patient experienced poor oxygenation and a decreased level of consciousness early in the morning following the laser irradiation. Nasal endoscopy revealed airway narrowing due to upper airway edema, and intubation was challenging. Consequently, we performed emergency bedside tracheostomy and the patient’s condition improved. Conclusion: Therefore, it is crucial to note that airway emergencies can be life-threatening and should be diligently monitored as a potential complication of PIT.